2015
DOI: 10.1108/compel-02-2015-0094
|View full text |Cite
|
Sign up to set email alerts
|

Artefact reduction in fast Bayesian inversion in electrical tomography

Abstract: Purpose-The purpose of this paper is to reduce the artifacts in fast Bayesian reconstruction images in electrical tomography. This is in particular important with respect to object detection in electrical tomography applications. Design/methodology/approach-The authors suggest to apply the Box-Cox transformation in Bayesian linear minimum mean square error (BMMSE) reconstruction to better accommodate the non-linear relation between the capacitance matrix and the permittivity distribution. The authors compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This method has been used for EIT, but not yet used for EITS other than in simulations [23,53]. It is well described in [7] and used in [68] for robotic applications. It is essentially an implementation of a Bayesian Linear Minimum Mean Square Estimation (BLMMSE) approach.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…This method has been used for EIT, but not yet used for EITS other than in simulations [23,53]. It is well described in [7] and used in [68] for robotic applications. It is essentially an implementation of a Bayesian Linear Minimum Mean Square Estimation (BLMMSE) approach.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…In this paper, we perform EITS by using a non-iterative method described in Zangl and Mühlbacher-Karrer (2015), called optimal first order approximation (OFOA), which is essentially an implementation of a Bayesian linear minimum mean square estimation approach. In addition to that, a planar electrode geometry is used instead of the traditional circular electrode geometry.…”
Section: Methodsmentioning
confidence: 99%
“…OA has already been tested on real experimental dataset with positive results [25,26,46] and a number of extensions have been made since its first appearance such as (i) dimension reduce x ∈ R n for further computational efficiency [28,29] (ii) reconstruct x with a variable electrode position on the surface [25] and (iii) estimate parameters related to permittivity in ECT such as volume fraction [41] and mass concentration [43], to name a few.…”
Section: X = B(y)mentioning
confidence: 99%
“…In OA, it was shown that a linear and quadratic operator B(y) worked well to obtain point estimates in ECT inverse problem [28,46,47]. Due to the close relation between ECT and EIT, we also investigate the fitting of linear, quadratic and cubic operators B(y) here.…”
Section: Choosing the Posterior Approximated Regression Modelmentioning
confidence: 99%